Improvement strategy of open space at the center of a traditional lowland town with narrow paths for securing persons in need of aids viewing from evacuation time - N. Mishima; Y. Taguchi; Y. Okazaki; H. Wakuya; K. Kitagawa; Y. Hayashida; Y.S. Oh; S.G. Park (International Association of Lowland Technology, 2015)
This paper aims to discuss improvement strategy of an existing open space at the center of a traditional lowland town, in which local spatial heritage including narrow paths should be preserved. We calculated evacuation times not only of normal persons but also of persons in need of aids on the assumption of street blockades in narrow paths might occur by disaster such as large earthquake also with big fire. In the study area, we thought that the weedy vacant space at the center worked as an efficient evacuation route for residents. Yet, the calculation results showed that the evacuation time of person in need of hard aids was more than we expected in the case of street blockades, although the others could. It means that it is useful to maintain the vacant space at the center in the town in order to secure evacuation without damage of the traditional meanings of the area in lowland, but that the other measurements are also necessary especially for person in need of hard aids.